Travel habits and complications in patients treated with vitamin K antagonists: A cross sectional analysis - Ringwald, Juergen; Lehmann, Marina; Niemeyer, Nicole; Seifert, Isabel; Daubmann, Anne; Wegscheider, Karl; Salzwedel, Annett; Luxembourg, Beate; Eckstein, Reinhold; Voeller, Heinz (Travel Medicine and Infectious Disease, 2014)
Travel-related conditions have impact on the quality of oral anticoagulation therapy (OAT) with vitamin K-antagonists. No predictors for travel activity and for travel-associated haemorrhage or thromboembolic complications of patients on OAT are known.A standardised questionnaire was sent to 2500 patients on long-term OAT in Austria, Switzerland and Germany. 997 questionnaires were received (responder rate 39.9%). Ordinal or logistic regression models with travel activity before and after onset of OAT or travel-associated haemorrhages and thromboembolic complications as outcome measures were applied.43.4% changed travel habits since onset of OAT with 24.9% and 18.5% reporting decreased or increased travel activity, respectively. Long-distance worldwide before OAT or having suffered from thromboembolic complications was associated with reduced travel activity. Increased travel activity was associated with more intensive travel experience, increased duration of OAT, higher education, or performing patient self-management (PSM). Travel-associated haemorrhages or thromboembolic complications were reported by 6.5% and 0.9% of the patients, respectively. Former thromboembolic complications, former bleedings and PSM were significant predictors of travel-associated complications.OAT also increases travel intensity. Specific medical advice prior travelling to prevent complications should be given especially to patients with former bleedings or thromboembolic complications and to those performing PSM.
EVALuna2:15980